2018
DOI: 10.1186/s12872-018-0919-9
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of STEMI patients with chronic kidney disease treated with percutaneous coronary intervention: the Malaysian National Cardiovascular Disease Database – Percutaneous Coronary Intervention (NCVD-PCI) registry data from 2007 to 2014

Abstract: BackgroundPatients with renal impairment often left out from most major clinical trials assessing the optimal treatment for ST-elevation myocardial infarction (STEMI). Large body of evidence from various cardiovascular registries reflecting more ‘real-world’ experience might contribute to the knowledge on how best to treat this special cohort. We aim to analyze the outcomes of Malaysian STEMI patients with renal impairment treated with coronary angioplasty.MethodsUtilizing the Malaysian National Cardiovascular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Studies focusing on STEMI-patients with advanced CKD are scarce. A registry analysis from Malaysia showed that STEMI-patients with advanced CKD had a worse prognosis and higher vascular complication-rates than patients with no CKD [ 25 ]. However, primary PCI-rates were comparatively low at 21% with high rescue PCI-rates after failed systemic fibrinolytic therapy at 70%.…”
Section: Discussionmentioning
confidence: 99%
“…Studies focusing on STEMI-patients with advanced CKD are scarce. A registry analysis from Malaysia showed that STEMI-patients with advanced CKD had a worse prognosis and higher vascular complication-rates than patients with no CKD [ 25 ]. However, primary PCI-rates were comparatively low at 21% with high rescue PCI-rates after failed systemic fibrinolytic therapy at 70%.…”
Section: Discussionmentioning
confidence: 99%
“…In that study, chronic renal failure was associated with more common myocardial infarction and a higher risk of death. Between 2007 and 2014, Ismail et al [21] investigated 6563 patients from the Malaysian National Cardiovascular Disease Database -Percutaneous Coronary Intervention (NCVD-PCI). The study showed a higher cardiovascular risk in patients with diabetes (54.6%), hypertension (79.2%), and dyslipidemia (68.8%).…”
Section: Discussionmentioning
confidence: 99%
“…For this study, the data of patients who underwent PCI from 2007 to 2014 in 15 participating hospitals across the country were retrospectively analyzed. The description of methods can also be found in previously published articles generated from this registry (12,13) and in the Annual Report of the NCVD-PCI registry year 2013-2014 (14).…”
Section: Study Populationmentioning
confidence: 99%
“…Consistent with previously published reports from NCVD-PCI registry, our cohort of patients are generally much younger than reports from other parts of the world by approximately 10 years. (12,14)There were significantly more old and female patients subjected to the femoral approach during cardiac catheterization likely because they tend to have difficult and complex vasculatures. In patients with higher BMI and taller, it was more commonly performed via a radial approach.…”
Section: Patient's Baseline Characteristicsmentioning
confidence: 99%